All Days 2003
DOI: 10.2118/80247-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Opportunities for the Drilling Industry Through Innovative Emulsifier Chemistry

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractAs the drilling industry operates in more stringent environmental constraints and conservative economical environment, the industry is poised to take advantage of innovative emulsifiers for new opportunities in solving the environmental problems and offer economical advantages over conventional invert emulsion drilling fluids. We have developed various innovative invert emulsion drilling fluids using novel emulsifiers. These systems provide a quantum leap in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Since commercial blends of surfactants were used in those studies, the actual chemical structures of the surfactants were not known. Patel and Ali (2003) suggested the use of ethoxylated amines as emulsifiers in drilling muds because it is possible to change their hydrophilic-lipophilic balance (HLB). Being able to manipulate the HLB value would allow one to alternate between an invert water-in-oil and oil-in-water emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Since commercial blends of surfactants were used in those studies, the actual chemical structures of the surfactants were not known. Patel and Ali (2003) suggested the use of ethoxylated amines as emulsifiers in drilling muds because it is possible to change their hydrophilic-lipophilic balance (HLB). Being able to manipulate the HLB value would allow one to alternate between an invert water-in-oil and oil-in-water emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules are reversible; that is, they are strong invert emulsifiers in the presence of a base but become regular emulsifiers in the presence of an acid ( Fig. 1) (Patel and Ali, 2003). It has been reported that this reversibility allows the drilling fluid to change from an invert emulsion, i.e., water-in-oil, to a regular emulsion, i.e., oil-in-water, at different stages of the drilling/completion operation.…”
Section: Introductionmentioning
confidence: 99%
“…During drilling, the drilling fluid can be used as an invert emulsion with all the performance benefits associated with oil-based muds (OBMs). During and after the completion stage, the emulsion can be reversed by adding a water-soluble acid, thus providing excellent filter-cake cleanup, better cementing, improved production in well completion, efficient cutting cleanup, and waste minimization (Ali et al, 2004(Ali et al, , 2006Green et al, 2001;Patel, 1999;Patel and Growcock, 1999;Patel and Ali, 2003). Because the unique attribute of RIEM in the completion of a well is supported by the pH-responsiveness of ethoxylated alkylamine emulsifiers, it is important to explore how pH levels influence the interfacial gathering behaviors of the emulsifiers and thus the completion performance of RIEM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since commercial blends of surfactants were used in those studies, the actual chemical structures of the surfactants were not known. Patel and Ali (2003) suggested the use of ethoxylated amines as emulsifiers in drilling muds because it is possible to change their Hydrophilic-Lipophilic Balance (HLB). Being able to manipulate the HLB value would allow one to alternate between an invert emulsion (water-inoil) and an emulsion (oil-in-water).…”
Section: Introductionmentioning
confidence: 99%